(untitled) (Malaysian Journal of Fundamental and Applied Sciences, 2023)
This research introduces an alternative approach on materials characterization by developing an in-house X-ray Absorption Spectroscopy (XAS) system utilizing powder X-ray Diffraction (XRD) machine. The performance of the in-house XAS system was investigated by analysing the position of Cu K-edge and the absorption spectrum shape within the X-ray Absorption Near Edge Structure (XANES) region. Copper (Cu) based samples were used to test the performance of the system where Cu and Copper Oxide (CuO) thin film deposited on polyimide tape and silicon wafer (100) prepared through the deposition process carried out using RF Magnetron Sputtering machine. Phase confirmation analysis were conducted by XRD and the deposited films’ thickness were measured by Scanning Electron Microscope (SEM). The laboratory-based XAS measurement was carried out using Rigaku SmartLab X-ray Diffractometer configured for Bragg-Brentano (BB) measurement mode. Molybdenum (Mo) target was used to produce white X-rays by energizing it near 20 keV ±0.01 keV. XRD measurements on XRD and SEM analysis proves successful deposition of pure Cu and CuO thin films and the film thickness measured is 1.432 μm and 0.680 μm respectively. The conclusive findings of the laboratory-based XAS measurements indicate successful acquisition of XAS data with similar spectrum shape of experimental Cu and CuO XANES in comparison with theoretical data. Next, experimental XANES shows clear observation of Cu K-edge peaks for Cu thin film at 8.9737 keV, while Cu K-edge for CuO thin films is not observable. Lastly, there is also presence of significant XANES broadening and which then effect consequent peak shiftings.